Direct determination of pyrazinamide (PZA) susceptibility by sputum microscopic observation drug susceptibility (MODS) culture at neutral pH: The MODS-PZA assay - Alcántara R. (2020)
Pyrazinamide (PZA) is considered the pivot drug in all tuberculosis treatment regimens due to its particular action on the persistent forms of Mycobacterium tuberculosis. However, no drug susceptibility test (DST) is considered sufficiently reliable for routine application. Although molecular tests are endorsed, their application is limited to known PZA resistance associated mutations. Microbiological DSTs for PZA have been restricted by technical limitations, especially the necessity for an acidic pH. Here, for the first time, MODS culture at neutral pH was evaluated using high PZA concentrations (400 and 800 _g/ml) to determine PZA susceptibility directly from sputum samples. Sputum samples were cultured with PZA for up to 21 days at 37°C. Plate reading was performed at two time points: R1 (mean, 10 days) and R2 (mean, 13 days) for each PZA concentration. A consensus reference test, composed of MGIT-PZA, pncA sequencing, and the classic Wayne test, was used. A total of 182 samples were evaluated. The sensitivity and specificity for 400 μg/ml ranged from 76.9 to 89.7 and from 93.0 to 97.9%, respectively, and for 800 μg/ml ranged from 71.8 to 82.1 and from 95.8 to 98.6%, respectively. Compared to MGITPZA, our test showed a similar turnaround time (medians of 10 and 12 days for PZAsensitive and -resistant isolates, respectively). In conclusion, MODS-PZA is presented as a fast, simple, and low-cost DST that could complement the MODS assay to evaluate resistance to the principal first-line antituberculosis drugs. Further optimization of test conditions would be useful in order to increase its performance. Copyright © 2020 Alcántara et al.